Antecedents That Affect Change In Organizational Performance - Zeeshan Malik; Syed Shoeb Ahmed Bokhari (Review Journal of Social Psychology & Social Works, 2025)
The efficiency of strategic management in an organization is because it offer formulas on how issues related to resources may e dealt with. Interest in factors that influence its total organisational performance today is a concern of all organisations. This study aimed at identifying the antecedent variables that predict endogenous organisational results. Consequently, the quantitative research method was used for the best implementation of the results. Out of 270 Volunteers randomly selected, the participants completed the sixty questionnaires that were issued to them. Out of 250 questionnaires given to the responders 20 questionnaires were not recovered; out of 250 questionnaires filled up 225 can be used and thus gives an 83% response rate. From the study the factors which determine the productivity of the organization have been outlined include environment, working condition, culture and politics, economy, human relation, organizational structure and organizational leadership. Based on the research it was recommended that the organisations must spend strategically more to cultivate more capital in assisting the staff members to fulfill their obligation as the department must endeavor to employ adequate manpower to meet the strategic directions set.